(untitled) (Conferencea, 2022)
In the study, the following general scientific methods were used: logical-historical method, pedagogical observation, analysis, synthesis, systematisation and generalisation, methods of pedagogical experiment, methods of mathematical statistics. The authors propose criteria and indicators of the readiness of future informatics teachers to develop electronic educational resources, as well as levels to identify the readiness of future informatics teachers to create electronic educational resources. In the paper, the authors share the results of an experiment to determine the suitability of their proposed methodology, describe the ways of forming the skills of future teachers to develop EER.